Navigation Techniques for the Visually Impaired implemented using Deep Learning : A Survey - S, Prabakaran; Tripathi, Samanvya; Nagpal, Utkarsh (International Journal of Psychosocial Rehabilitation, 2020)
Navigation plays a major role in the life of visually impaired people as they cannot get around easily without the assistance of escorts and hence, they must rely on their sense  of touch and hearing in order to tackle the obstacles on their way. The use of guide dogs, sticks have not proven helpful. They are not able to make the visually impaired individuals depend on themselves. In order to solve these problems, there are sev- eral computing techniques explored for real-time navigation for visually impaired such as Artificial Intelligence, Deep Learning, Machine Learning. With the help of deep learning algorithms, it is easy to identify different objects and these algorithms can be implemented in the form of a mobile navigation application. In this paper, we review existing techniques related to Deep Learning and try to enhance the experience for the visually impaired.